Polyphony, rhetoric and pluritextuality in 21st century brand communication: A systematic literature review - Milton Vásquez Patiño; Lorena Martínez-Soto; Nelly Rosario Moreno-Leyva (My University, 2025)
In the 21st century, brand communication has been significantly transformed through the interaction of users and artificial intelligence (AI), who co-create and recreate texts in digital environments. This evolution challenges traditional disciplines and roles, opening new perspectives for textual production on multiple platforms. The study examines the current state and application of the textual component in brand communication, exploring its disciplinary foundations, rhetorical traces, and research methodologies. To this end, a content analysis of 97 relevant publications from 2000 to 2024 was conducted, selected for their impact on the field of brand communication and following the guidelines established in the PRISMA statement. The results identified three sources of textual creation: Organization, users and algorithms. In addition, persuasion and sentiment take precedence at the rhetorical level, while data mining stands out in message analysis. In conclusion, the advertising text, which previously prevailed in brand communication with corporate authorship, formal prefiguration and a closed entity, now expands in a media and networked context. This text originates from a multiplicity of human and automated sources, overlapping rhetorical phases and fluid textualities. The shift implies a transition from unidirectional communication, characterized by repeated impacts, to multidirectional communication with spiraling trajectories and iterative adjustments. This challenges the boundaries of genres and formats, merging the persuasiveness of rhetoric and the imagination of storytelling. This situation demands commercial policies that integrate new professionals and roles, in partnership with the educational sector, and that address copyright with AI and users.
Keywords: Rhetorical question; Rhetoric; Polyphony; Storytelling; Context (archaeology); Persuasion; Discipline; Human communication; Computer science; Sociology; Public relations; Political science; Psychology; Communication; Linguistics; Narrative; Social science; Social psychology; Paleontology; Philosophy; Biology; Pedagogy; Rhetorical question; Rhetoric; Polyphony; Storytelling; Context (archaeology); Persuasion; Discipline; Human communication; Computer science; Sociology; Public relations; Political science; Psychology; Communication; Linguistics; Narrative; Social science; Social psychology; Social Sciences Social Sciences Sociology and Political Science Digital Marketing and Social Media; Social Sciences Social Sciences Communication Communication and COVID-19 Impact; Social Sciences Business, Management and Accounting Marketing Consumer Behavior in Brand Consumption and Identification